BrdU incorporation in multiparameter flow cytometry: a new cell cycle assessment approach in multiple myeloma - Requirand, Guilhem; Robert, Nicolas; Boireau, Stéphanie; Vincent, Laure; Seckinger, Anja; Bouhya, Salaheddine; Ceballos, Patrice; Cartron, Guillaume; Hose, Dirk; Klein, Bernard; Moreaux, Jérôme (Cytometry. Part B, Clinical cytometry, 2019)
Background Mutiple myeloma (MM) is a neoplasia characterized by the accumulation of malignant plasma cells (PC) in the bone marrow. Although proliferation markers have been studied in MM, none of the current staging systems include them. Moreover, approaches used to analyze proliferation do not separate MM cells (MMCs) from normal PC. Methods In this study, we combined multiparameter flow cytometry and BrdU incorporation or Ki67 staining to analyze MM cell proliferation in 44 monoclonal gammopathy of undetermined significance (MGUS), 153 newly diagnosed MM patients and 69 MM patients at relapse. The prognostic value of proliferation assessment was analyzed in 60 newly diagnosed patients treated with high-dose chemotherapy supported by autologous hematopoietic stem cell transplantation. Results The median number of proliferating malignant PC significantly increases during MM disease progression. MM patients with a percentage of proliferating MMCs greater than 1.42% using BrdU/DAPI or greater than 1.1% using ki67/DAPI, are associated with a significantly shorter event free survival compared with patients with a lower percentage of proliferating MMCs. Conclusions Combination of flow cytometry with BrdU or ki67/DAPI staining could become a standard for the determination of MM cell proliferation. Furthermore, in the context of new effective myeloma treatment options, assessment of MM cell proliferation may be valuable, in clinical trials, to identify novel agents that could significantly affect the small proliferative compartment of MM cells. © 2018 International Clinical Cytometry Society.
Gesehen am 25.10.2019
Published online: 12 November 2018